(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the activity of these compounds on sexual forms of Plasmodium falciparum and to determine the theoretical pharmacokinetic properties of the compounds using in silico assays. Methods: In order to evaluate the inhibition of exflagellant forms, Plasmodium falciparum strain NF54 was used for the production of gametocytes in vitro. The program ADMETlab was used in in silico tests to identify the theoretical pharmacokinetic properties of all compounds. Results: A number of tested natural and synthetic amides do not stand out as possible blockers of malaria transmission. However, they showed moderate inhibition in blocking exflagellation. The results of the virtual screening allowed to know and explore interesting theoretical pharmacokinetic properties of this class of compounds, such as moderate permeability with Caco-2 cells of compound 14f; all can be harmful but non-lethal (LD50); only compound 14f can cause damage to some food (LHID); compounds 1a, 1b, 1g and 1k can be administered at their daily maximum, always noting, 1g and 1k can be administered at their daily maximum; low throughput (CL); high plasma protein binding for compounds 1a, 14f and 18a; optimal distribution volume for 1b, 1g, 1k, 18a and 18b. Final considerations: The results obtained contribute to expand the database on the profile of this class of compounds and antimalarial action.